The Influence of Work-Life Balance and Work Motivation on Quality of Work Life Among Single Mothers Employed in Multinational PR Agencies in South Jakarta - Asrini Mahdia (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine the influence of work-life balance and work motivation on the quality of work life (QWL) among single mothers working in multinational Public Relations (PR) agencies in South Jakarta. The participants were 20 single working mothers who had been employed for over one year, selected through purposive sampling. A quantitative correlational approach was employed using Likert-scale questionnaires. Pearson correlation and multiple regression analysis revealed that both work-life balance and work motivation were positively and significantly correlated with quality of work life. These findings suggest that a better balance between work and personal life and stronger work motivation contribute to a higher quality of work life for single mothers in high-pressure professional settings.